2022
DOI: 10.21203/rs.3.rs-1385351/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of information sources on COVID-19 Vaccine hesitancy and resistance in Sub- Saharan Africa

Abstract: Background Vaccination remains the most powerful weapon against the emergence of new variants of coronavirus (COVID-19). However, false information about COVID-19 vaccines through various platforms including social media remain a major threat to global public health. The study examined the impact of information sources on COVID-19 vaccine hesitancy and resistance in sub-Saharan Africa (SSA). Methods A validated web-based questionnaire was administered in French and English to 2572 participants from sub-Sahar… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
1
3
0
2
Order By: Relevance
“…In addition, a plethora of studies across the globe have shown that the use of social media is strongly associated with increased COVID-19 vaccine hesitancy [35][36][37]. Our findings are in line with previous research and highlight the challenges of improving COVID-19 vaccine uptake on the African continent against this background [5][6][7].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In addition, a plethora of studies across the globe have shown that the use of social media is strongly associated with increased COVID-19 vaccine hesitancy [35][36][37]. Our findings are in line with previous research and highlight the challenges of improving COVID-19 vaccine uptake on the African continent against this background [5][6][7].…”
Section: Discussionsupporting
confidence: 89%
“…The delayed roll-out of COVID-19 vaccines in African countries has left the population vulnerable to new surges in infections by COVID-19 variants throughout the pandemic. The situation has been further exacerbated by prevalent vaccine hesitancy and lack of confidence in COVID-19 vaccines, mainly fueled by exposure to inundating misinformation on COVID-19 and COVID-19 vaccines through online and other sources [5][6][7], against an already concerning backdrop of overall hesitancy toward new vaccines in Africa [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for this discrepancy may be due to the fact that COVID-19 virus in sub-Saharan Africa may not be regarded as dangerous as it is in other countries. For example, a study by Osuagwu et al (2022) showed that 72.2 and 84.5% of sub-Saharan people were resistant to or hesitant about COVID-19 vaccination, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Parte de los resultados obtenidos en la investigación desarrollada a una muestra de 219 personas en el departamento de Córdoba, Colombia, muestra un impacto significativo en algunas variables sociales analizadas, las siguientes son las preguntas relacionadas con factores como ansiedad, depresión, relaciones personales, vida social y salud mental, donde podemos ver el grado de impacto que ocasionó el Covid-19 en la vida de los habitantes de esta región del caribe Colombiano; en el gráfico 1 y 2 vemos que los niveles de ansiedad y depresión han incrementado sustancialmente en 65.3% y 48.9% pág. 1178 respectivamente, lo que refleja que más de la mitad de la población está padeciendo estos trastornos producto de la pandemia y sus secuelas, estos resultados se relacionan con información encontrada en otros continentes como África en donde se evidenció altos niveles de estrés en la población estudiada, en este caso producto de las informaciones que recibían en diferentes medios de comunicación sobre lo que estaba pasando con la pandemia (Osuagwu et al, 2023).…”
Section: Resultsunclassified